Development of a training program for clinical instructors in Physical Therapy - Agcaoili, Jocelyn F. (2000)
A diagnostic survey was done among the clinical instructors (CIs) in the physical therapy affiliation centers where the University of Santo Tomas B.S. Physical Therapy interns affiliate in order to establish their training needs in clinical teaching and evaluation. A questionnaire was completed by 46 clinical instructors in 15 affiliation centers. The results were organized and summarized using measures of central tendencies and frequency distributions. All of the respondents did not have any teacher training prior to assuming responsibilities as CIs. Some CIs admitted that they were not aware of some of the functions of a clinical instructor. Majority admitted that they experienced difficulties and lacked the necessary confidence in the performance of their teaching duties including planning instruction, implementing instructional activities and evaluation of student's performance. Based on the results of the survey, an appropriate training program was then developed. As designed, the training program focused on instructional planning, methods and techniques of clinical teaching, proper communication and methods and tools of evaluation.
Major project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Physical therapy -- Study and teaching (Residency)